Quality planting materials for cassava, sweetpotato and yam. Rapid virus elimination for crop improvement and seed systems. Project profile - International Potato Center (International Potato Center, 2019)
Virus screening and elimination are necessary steps to prevent the spread of diseases when moving plant material from place to place. However, these measures can cause long delays in the release of new varieties. This project seeks to develop improved methods for disease detection, as well as phytosanitary cleaning of plant material that speed up the process of producing high-quality, diseasefree stock for breeding trials and for farmers.